The Social Economy in Spain: Special Reference to Workers Cooperatives - Valdueza Blanco, María Dolores (2016)
This article addresses the issue of cooperatives in the context of global economic crisis and presented as a suitable alternative to deal with high unemployment, and as the fulfillment of a social economy, protected and provided for by law and the Spanish constitution. Will be discussed the characteristics of cooperatives, its constitution and its organization. In addition, there will be mention of types of cooperatives, especially the cooperative mode of worker cooperatives.